2008
DOI: 10.1007/s10508-008-9434-x
|View full text |Cite
|
Sign up to set email alerts
|

Asexuality: A Mixed-Methods Approach

Abstract: Current definitions of asexuality focus on sexual attraction, sexual behavior, and lack of sexual orientation or sexual excitation; however, the extent to which these definitions are accepted by self-identified asexuals is unknown. The goal of Study 1 was to examine relationship characteristics, frequency of sexual behaviors, sexual difficulties and distress, psychopathology, interpersonal functioning, and alexithymia in 187 asexuals recruited from the Asexuality Visibility and Education Network (AVEN). Asexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
220
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(243 citation statements)
references
References 54 publications
18
220
0
5
Order By: Relevance
“…There remain inconsistent operational definitions of asexuality within research, as will be discussed below, though it is commonly defined as a lack of sexual attraction toward others (Bogaert, 2004;Bogaert, 2006;Brotto, Knudson, Inskip, Rhodes, & Erskine, 2010). Studies have reported that a sizeable minority of the population lacks sexual attraction toward others.…”
Section: Implicit and Explicit Attitudes Toward Sex And Romance In Asmentioning
confidence: 99%
See 3 more Smart Citations
“…There remain inconsistent operational definitions of asexuality within research, as will be discussed below, though it is commonly defined as a lack of sexual attraction toward others (Bogaert, 2004;Bogaert, 2006;Brotto, Knudson, Inskip, Rhodes, & Erskine, 2010). Studies have reported that a sizeable minority of the population lacks sexual attraction toward others.…”
Section: Implicit and Explicit Attitudes Toward Sex And Romance In Asmentioning
confidence: 99%
“…Previous studies have considered asexuality to be a lack of sexual activity (Rothblum & Brehony, 1993), a lack of sexual attraction (Bogaert, 2004;Brotto et al, 2010), a lack of sexual desire (Prause & Graham, 2007), having little to no sexual attraction and/or self-identifying as asexual (Chasin, 2011), the opposite of bisexuality (Carrigan, 2011;Storms, 1980), or have combined measures of behaviour, desire, and self-identification (Poston Jr & Baumle, 2010).…”
Section: Asexuality Definedmentioning
confidence: 99%
See 2 more Smart Citations
“…The only shared demographic point of note across these studies is that women are more likely both to selfidentify as asexual and to be defined as such. A further methodological problem with these studies is that they have tended to use measures that reflect dominant sexualised approaches (Hinderliter 2009 Brotto et al 2010). This reflects a wider lack of methodological plurality in research on asexuality (Carrigan, Gupta and Morrison 2013:116-117).…”
Section: Psychological and Sexological Theoriesmentioning
confidence: 99%